Contextualised high-intensity running profiles of elite football players with reference to general and specialised tactical roles - Ju, Wonwoo; Doran, Dominic; Hawkins, Richard; Evans, Mark; Laws, Andy; Bradley, Paul (Biology of Sport, 2023)
The present study aimed to contextualise physical metrics with tactical actions according to general and specialised tactical roles. A total of 244 English Premier League players were analysed by coding player’s physical-tactical actions via the fusion of tracking data and video. Data were analysed across 5 general (Central Defensive Players = CDP, Wide Defensive Players = WDP, Central Midfield Players = CMP, Wide Offensive Players = WOP, Central Offensive Players = COP) and 11 specialised positions (Centre Backs = CB, Full-Backs = FB, Wing-Backs = WB, Box-to-Box Midfielders = B2BM, Central Defensive Midfielders = CDM, Central Attacking Midfielders = CAM, Wide Midfielders = WM, Wide Forwards = WF, Centre Forwards = CF). COP covered more distance at high-intensity (> 19.8 km· h-1) when performing actions such as ‘Break into Box’, Run in Behind/Penetrate’, and ‘Close Down/Press’ than other positions (ES: 0.6–5.2, P < 0.01). WOP covered more high-intensity ‘Run with Ball’ distance (ES: 0.7–1.7, P < 0.01) whereas WDP performed more ‘Over/Underlap’ distance than other positions (ES: 0.9–1.4, P < 0.01). CDP and WDP covered more high-intensity ‘Covering’ distances than other positions (ES: 0.4–2.4, P < 0.01). Nonetheless, data demonstrated that implementing specialised positional analysis relative to a generalised approach is more sensitive in measuring physical-tactical performances of players with the latter over or underestimating the match demands of the players compared to the former. A contextualised analysis may assist coaches and practitioners when designing position or even player-specific training drills since the data provides unique physical-tactical trends across specialised roles.